The Impact of Trade Deficit in Nepalese Economy - Mansuri, Jabed (Journal of Management, 2021)
This study aims to explore more information about the economic performance of Nepal and the impact on the economy caused by foreign trade. The trade deficit impacted directly on the financial performance of the country. It affected the GDP of the nation, supply side, interest rate, price of commodities and FDI. The article has discussed the relationship with the major trading partner of Nepal and other countries. Besides this, a quantitative research method was used in this research paper. Information in this article was collected from a secondary source of data. The reliability of this study depended on the reliability of secondary data. The analysis was based on a simple statistical tool. Concerning the methodology, it is based on exploratory data analysis. The comparison has been made in this paper with primary trading partner countries India, China and other countries. This study has found the deficient export performance of Nepal, which has created the problem of rapidly increasing trade deficit. Trade deficit became one of the major causes that lead the national economy to downturn side.